Students' Language Politeness in the Independent Curriculum in Class V of SDN 4 Cacaban, Magelang City - Jendriadi Jendriadi; Farikah Farikah; Triantono Triantono; Delfiyan Widiyanto; Ipung Hananto; Linda Eka Pradita; Umi Rachmawati (EduLine: Journal of Education and Learning Innovation, 2023)
Language politeness is one of the skills that every person needs to apply . An impolite individual can be said to be an individual who is unable to appreciate, respect and sympathize with other individuals. Politeness in oral communication will have an effect on students' communication activities when dealing with various parties in everyday life . Factors that influence students' politeness come from parents, social environment, norms in society , and understanding of the principles of language politeness. Today's situation is that many students are not good at sorting and choosing words when interacting with people older than them. Their teachers are no exception. Therefore, it is necessary to observe students' language politeness so that they can interact well with any party. This research aims to observe the language politeness activities of class V students at SDN 4 Cacaban, Magelang city . The method used is a descriptive qualitative method as an effort to describe the politeness of students' language. Based on the research results, it shows that the language politeness applied by class V students in the independent curriculum is in accordance with the types of politeness acts . In the research conducted, it appears that teachers also play a role in influencing students' language politeness. Teachers also use polite greetings , by asking for help from their students. In this case, the teacher acts as an example and provides guidance to students regarding the importance of language politeness .